All these voices in my head - Lim, Min Ming (2018)
All These Voices in My Head is a personal exploration at documenting my inner voices (defined as passing thoughts and emotions). As an attempt to quiet these inner voices, I begun the practice of mindfulness meditation and explores a framework of forty days for this experiment. To track my progress of the practice, documentation of occurring thoughts and emotions each day were analysed, categorised and translated into visuals. This process was later developed into an app to extend the practice and visualisation to a larger audience. By connecting users of this app through an online repository, the project aims to map and understand the society’s collective inner voices.